A political satire against the Peru-Bolivian Confederation: La Mulata (1838) edited by Buenaventura Seoane - Peralta Ruiz, Víctor (2017)
This article analyses the contents of an unknown conservative newspaper entitled La Mulata that was against the Peru-Bolivian Confederation in October 1828. It was edited in Lima by the lawyer and politician Buenaventura Seoane. Thecontents of the five numbers of La Mulata show that it was a newspaper for propaganda and political satire. Particularly, it focused on afro-descendant people, especially former slaves or libertos, to demonstrate how the lower sectors of the population can amend the loss of political freedom by adopting a patriotic attitude. La Mulata provides new insights to understand the political rhetoric of the Peruvian creolle nationalism in the first half of the nineteenth century.